Interleukin-8 Release Inhibitors Generated by Fermentation of Artemisia princeps Pampanini Herb Extract With Lactobacillus plantarum SN13T - Okamoto, Tomoko; Sugimoto, Sachiko; Noda, Masafumi; Yokooji, Tomoharu; Danshiitsoodol, Narandalai; Higashikawa, Fumiko; Sugiyama, Masanori (Frontiers in Microbiology, 2020)
Some glycosides, which are detected in water extracts from medicinal plants, have been reported to be degraded into their aglycones by incubating with some microorganisms producing β-glucosidase. We have shown that a plant-derived Lactobacillus plantarum SN13T harbors eleven open reading frames (ORFs) encoding the β-glucosidase enzyme and can grow vigorously in several herbal water extracts. In this study, we observed that the water extract from Artemisia princeps Pampanini (AP) fermented with the SN13T strain strongly inhibited the release of interleukin (IL)-8 from the HuH-7 cells, when compared to that without fermentation. Furthermore, we demonstrated that the SN13T strain produced at least two bioactive compounds from some compounds contained in AP extract. In addition, we determined that the two compounds were catechol and seco-tanapartholide C, which dose-dependently inhibited the release of IL-8. Because some sesquiterpene lactones are useful as pharmaceuticals, seco-tanapartholide C may be useful as an anti-inflammatory agent. This study suggests the fermentation of medicinal herbs with Lb. plantarum SN13T is a significant technique to obtain bioactive compounds having therapeutic potential.